15 Non-ischaemic cardiomyopathy and cardiac resynchronization therapy– revisiting the 'at risk' patient profile. (October 2018) - Voon, V; Lau, WY; Pereira, H; Shanmugam, N; Ray, R; Anderson, L
Abstract : Background: Non-ischaemic cardiomyopathy has been associated with better left ventricular (LV) remodeling and outcomes post-cardiac resynchonization therapy (CRT) but has separately been linked to poorer outcomes when associated with mid-wall fibrosis (MWF) on cardiac magnetic resonance. Therefore, we aimed to confirm the impact of MWF in patients with non-ischaemic cardiomyopathy and CRT. Methods: We retrospectively evaluated data from 110 consecutive patients with a diagnosis of non-ischaemic cardiomyopathy and CRT implants. Non-eligible patients were excluded (eg. ischaemic, amyloid or sarcoid cardiomyopathy, missing data). Patients with or without mid wall fibrosis (MWF+, n=57 vs MWF-, n=53), were compared and evaluated for long-term outcomes of all-cause mortality or hospitalizations for ventricular arrthythmias or heart failure from time of CRT implant (figure 1). Results were reported as mean ±SD. p≤0.05 was deemed statistically significant. Results: Mean age of patient cohort was 67±14 years with total follow-up duration of 900±692 days. Between the groups, no significant difference in baseline demographics was observed in terms of age, gender, comorbidities (hypertension/diabetes), medication profiles, electrocardiographic measures (intrinsic rhythm and QRS duration), and LV ejection fraction. However, MWF+ demonstrated higher LV end-diastolic volume and LV end-systolic volume compared to MWF- (271±81 vs. 232±85 ml; 193±79 vs 160±79 ml, respectively, all p<0.05). Despite that, there were no significant between-group differences in all-cause mortality or hospitalizations for ventricular arrhythmia or heart failure over the follow-up duration. Conclusion: This retrospective study showed that MWF+ was associated with higher LV end-diastolic volumes and end-systolic volumes compared to MWF-. However, no significant impact was observed in MWF+ on long-term cardiac outcomes in patients with non-ischaemic cardiomyopathy and CRT. Further evaluation in larger studies is warranted.